All 17 S‐locus F‐box proteins of the S2‐ and S3‐haplotypes of Petunia inflata are assembled into similar SCF complexes with a specific function in self‐incompatibility. (5th August 2016) - Li, Shu; Williams, Justin S.; Sun, Penglin; Kao, Teh‐hui
Summary: The collaborative non‐self‐recognition model for S‐RNase‐based self‐incompatibility predicts that multiple S‐locus F‐box proteins (SLFs) produced by pollen of a given S ‐haplotype collectively mediate ubiquitination and degradation of all non‐self S‐RNases, but not self S‐RNases, in the pollen tube, thereby resulting in cross‐compatible pollination but self‐incompatible pollination. We had previously used pollen extracts containing GFP‐fused S2 ‐SLF1 (SLF1 with an S 2 ‐haplotype) of Petunia inflata for co‐immunoprecipitation (Co‐IP) and mass spectrometry (MS), and identified PiCUL1‐P (a pollen‐specific Cullin1), PiSSK1 (a pollen‐specific Skp1‐like protein) and PiRBX1 (a conventional Rbx1) as components of the SCF S 2– SLF 1 complex. Using pollen extracts containing PiSSK1:FLAG:GFP for Co‐IP/MS, we identified two additional SLFs (SLF4 and SLF13) that were assembled into SCF SLF complexes. As 17 SLF genes ( SLF1 to SLF17 ) have been identified in S 2 and S 3 pollen, here we examined whether all 17 SLFs are assembled into similar complexes and, if so, whether these complexes are unique to SLFs. We modified the previous Co‐IP/MS procedure, including the addition of style extracts from four different S ‐genotypes to pollen extracts containing PiSSK1:FLAG:GFP, to perform four separate experiments. The results taken together show that all 17 SLFs and an SLF‐like protein, SLFLike1 (encoded by an S ‐locus‐linked gene), co‐immunoprecipitated with PiSSK1:FLAG:GFP. Moreover, of the 179 other F‐box proteins predicted by S 2 and S 3 pollen transcriptomes, only a pair with 94.9% identity and another pair with 99.7% identity co‐immunoprecipitated with PiSSK1:FLAG:GFP. These results suggest that SCF SLF complexes have evolved specifically to function in self‐incompatibility. Significance Statement: Seventeen types of pollen‐specific S‐locus F‐box proteins (SLFs) of S 2 ‐ and S 3 ‐haplotypes collectively mediate ubiquitination and degradation of respective non‐self S‐RNases to allow cross‐compatible pollination. In this work, we report that, all 17 types of SLFs, an SLF‐like protein, and only four of the 179 non‐SLF F‐box proteins predicted to be expressed in pollen, are assembled into similar SCF complexes, suggesting that these complexes specifically evolved to function in self‐incompatibility.